Influence of Cultural and Pest Management Practices on Performance of Runner, Spanish, and Virginia Market Types in North Carolina - Bridget R. Lassiter; David L. Jordan; Gail G. Wilkerson; Barbara B. Shew; Rick L. Brandenburg (Advances in Agriculture)
Virginia market type peanut (Arachis hypogaea L.) cultivars are grown primarily in North Carolina, South Carolina, and Virginia in the US, although growers in these states often plant other market types if marketing opportunities are available. Information on yield potential and management strategies comparing these market types is limited in North Carolina. In separate experiments, research was conducted to determine response of runner, Spanish, and Virginia market types to calcium sulfate and inoculation with Bradyrhizobium at planting, planting and digging dates, planting patterns, and seeding rates. In other experiments, control of thrips (Frankliniella spp.) using aldicarb, southern corn rootworm (Diabrotica undecimpunctata Howardi) using chlorpyrifos, eclipta (Eclipta prostrata L.) using threshold-based postemergence herbicides, and leaf spot disease (caused by the fungi Cercospora arachidicola and Cercosporidium personatum) fungicide programs was compared in these market types. Results showed that management practice and market types interacted for peanut pod yield in only the planting date experiment. Yield of runner and Virginia market types was similar and exceeded yield of the Spanish market type in most experiments.